1997
DOI: 10.4141/s94-083
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of canola residues: Release of water-soluble phytotoxins

Abstract: Wanniarachchi, S. D. and Voroney, R. P. 1997. Phytotoxicity of canola residues: Release of water-soluble phytotoxins. Can. J. Soil Sci. 77: 535-541. Phytotoxicity of root, stem and leaf residues of canola (Brassica napus L.) was studied in a laboratory incubation for 8 wk. Bioassays were conducted with corn (Zea mays L.), barley (Hordeum vulgare L.) and wheat (Triticum aestivum L.) seeds to determine the relative toxicity of residue extracts. The release of volatile fatty acids (VFAs) and phenolic compounds (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…Water-soluble extracts from canola root, stem and leaf tissues suppressed the growth of wheat, barley and corn seedlings, even after only one day of incubation 16 . Extracts of canola leaves were the most phytotoxic to the seedlings, causing decreased coleoptile and radicle elongation compared to the control 16 . Similarly, water-soluble extracts from dead black mustard stalks and leaves were effective Table 1.…”
Section: Growth Of Established Seedlingsmentioning
confidence: 97%
See 1 more Smart Citation
“…Water-soluble extracts from canola root, stem and leaf tissues suppressed the growth of wheat, barley and corn seedlings, even after only one day of incubation 16 . Extracts of canola leaves were the most phytotoxic to the seedlings, causing decreased coleoptile and radicle elongation compared to the control 16 . Similarly, water-soluble extracts from dead black mustard stalks and leaves were effective Table 1.…”
Section: Growth Of Established Seedlingsmentioning
confidence: 97%
“…Members of the Brassicaceae family contain glucosinolates-sulfur-containing molecules that are hydrolyzed to form compounds toxic to a variety of soil-borne organisms, including weeds 9 . Laboratory and greenhouse studies suggest that the hydrolysis products of glucosinolates, as well as brassica residues and extracts containing these compounds, are toxic to weeds [10][11][12][13][14][15][16] , insect pests 17,18 and pathogens [19][20][21] . In addition, a limited number of field studies have confirmed the ability of brassicas in rotations to suppress weeds [22][23][24] , nematodes 25 and fungal pathogens 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in particular environmental conditions, we cannot exclude that the phytotoxicity of VFAs generated from hydrochar after its application to the soil could be enhanced. On the other hand, soil biological (e.g., microbial composition and activity) and physical conditions may also play an opposing role by decreasing the production or buffering the phytotoxic effect of VFAs in agricultural soils, as demonstrated by several incubation studies [51].…”
Section: Fresh Hydrochar (Fh) Chemical Propertiesmentioning
confidence: 99%
“…These findings are in agreement with that found by Mian and Rodríguez-Kábana (1982) or Hewlett et al (1997), on other crops, where the use of higher amount of tannins showed phytotoxic effect on growth parameters of squash and tomato plants, respectively. Some residues of plants contain volatile fatty acids (VFAs) and phenolic compounds (PCs) which are phytotoxic on other plant species growth as found by Wanniarachchi and Voroney (1997). They tested the release of VFAs and PCs from root, stem and leaves residues of canola plants (rapeseed) (Brassica napus L.) and their inhibiting (P≤0.01) effect on seedling growth (coleoptile and radicle lengths) of corn (Zea mays L.), barley (Hordeum vulgare L.) and wheat (Triticum aestivum L.) plants.…”
Section: Discussionmentioning
confidence: 99%